Internalisasi Nilai-Nilai Gender Melalui Aktivitas Literasi Dalam Keluarga Pegiat Literasi Makassar - Harnita Rahman; M. Tamar; M.E. Fachry (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
This study aims to identify gender values through literacy activities and analyze their effects on gender relations in literacy activist families in Makassar. This research is a qualitative research using descriptive analysis. Data obtained through literature review, interview and observation. The informants were selected by purposive sampling by determining 2 families of literacy activists, namely Paradigma Institute and Kampung Buku in Makassar City, South Sulawesi. The data were processed using coding techniques and analyzed using family ecology theory and socialist feminist theory. The results showed that literacy activities in the form of the establishment of libraries and initiation of learning spaces carried out by literacy activists in their homes, contained gender values namely openness, equality, and cooperation. Internalization of gender values through literacy activities affects the gender relations between husband, wife and children in the family. This form of internalization of values is reflected in the decision making process in determining education and childcare as well as in the division of labor in the household.